Efecto de la inversión extranjera directa en el desempleo de Ecuador: mediante técnicas de cointegración, periodo 1985-2019. - García Ambrossi, Dunnya Sophía (2022)
Foreign Direct Investment (FDI) is one of the factors that influences unemployment, which is why this research focuses on studying the impact of FDI on unemployment in Ecuador during the period 1985-2019. For its realization, data from the World Bank (WB, 2021) was taken, having unemployment as the dependent variable, FDI as the independent variable, and additionally the control variables, remittances, total natural resources income, exports and public expenditure. The methodology used includes evolution and correlation graphs, an Ordinary Least Squares (OLS) model, which determines the relationship of the variables; an error correction model (ECV), and Vector Autoregressive (VAR) to determine the relationship in the short and long term; and finally, a causality test. The results showed that FDI has a positive effect on unemployment, a short- and long-term relationship is also found, and no causality between the theoretical variables of the model, but unidirectional causality was found between unemployment towards natural resource rents, and towards exports, as well as between natural resource rents and FDI. Based on these results, it is suggested to generate different economic policy mechanisms that facilitate the improvement and control of macroeconomic indicators to make it more attractive for foreign investors to make decisions.